LEADERSHIP STYLE ANALYSIS OF EMPLOYEE PERFORMANCE MOTIVATION AT TIGARUNGGU PUSKESMAS - Mayanti Sirait, Sri (RADJA PUBLIKA, 2022)
An organization must have a leader who is able to direct and guide employees in the organization. The relationship between leadership style and employee performance motivation is where the higher the performance motivation of an employee at work, the resulting performance will also be more effective and competent in his field of work. This study aims to determine the analysis of leadership style on employee performance motivation at Tigarunggu Public Health Center in 2020. With a sample of 30 people. The data collection tool used was a questionnaire and data analysis was carried out univariately using data processing. The results of the chi-square test analysis can be obtained that leadership style has a relationship with the performance motivation of Tigarunggu Public Health Center employees in 2020.